ANALISIS PENGEMBANGAN DIRI PADA KOMPETENSI PEDAGOGIK GURU SMA MODEL DI KOTA PALEMBANG - Dian Eka Amrina; Edutivia Mardetini (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2019)
This study aims to describe the development of self in pedagogical competencies carried out by economic subject teachers as well as supporting and inhibiting factors in developing themselves in the SMA Kota Palembang Model. This study uses a qualitative approach with a case study method. The research subjects were determined using purposive sampling so that three teachers were certified on economic subjects at SMAN 4 Palembang. Data collection techniques used are interviews, and documentation. The data analysis technique uses the Miles and Huberman models. Self-development in the pedagogical competence of the teacher is still focused on the intensive activities held by the school, and has not touched cooperative and independent activities. Supporting factors for self-development are the opportunities provided by Palembang N 4 High School to develop themselves. While the inhibiting factor is the lack of participation from the government for self-development activities and lack of motivation from educators to develop self-competence through independent activities.